2019
DOI: 10.1111/opn.12260
|View full text |Cite
|
Sign up to set email alerts
|

How smart homes are used to support older people: An integrative review

Abstract: Background The number of healthy older people is increasing, and most of them want to live in their own homes for as long as possible. Smart home technology can support living at home, but synthetised knowledge of previous studies about their suitability for the everyday lives of older people is rare. Methods Data for this integrated review were obtained by searching the PubMed, CINAHL and Scopus databases from 2012 to 2019, based on inclusion and exclusion criteria, and then carrying out quality appraisals of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 44 publications
2
50
0
4
Order By: Relevance
“…The older adults referred to security and safety as the top value. According to Turjamaa et al [ 68 ], older people reported that smart homes improved their sense of security at home (especially if they lived far away from their relatives), as well as their quality of daily life and activities, and provided them with information about the care they could receive. Therefore, the smart home solutions would be designed to help older people carry out everyday activities and lead healthier and more fulfilled lives, by improving their physical safety and social communication.…”
Section: Discussionmentioning
confidence: 99%
“…The older adults referred to security and safety as the top value. According to Turjamaa et al [ 68 ], older people reported that smart homes improved their sense of security at home (especially if they lived far away from their relatives), as well as their quality of daily life and activities, and provided them with information about the care they could receive. Therefore, the smart home solutions would be designed to help older people carry out everyday activities and lead healthier and more fulfilled lives, by improving their physical safety and social communication.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other home service systems, the system designed in this paper has a better user experience, making the user's life more comfortable, convenient, safe, and fun. Reference [7] Temperature and humidity measurement, camera, light control, flame/smoke alarm, human body infrared sensor * * *…”
Section: Discussionmentioning
confidence: 99%
“…With the development of electronic information technology and the improvement of people's living standards, people are increasingly yearning for the life of smart home [7]. e concept of smart home is to integrate different services in one home by using a common communication system [8].…”
Section: Related Workmentioning
confidence: 99%
“…It can also be used as a means to support communication, mobility, recreation [18] and increase social contact later in life [19]. However, despite significant development over the years [20][21][22][23], most technologies continue to be developed without much consideration of the ageing process and how it may impact its use by older adults [20,24,25].…”
Section: Technology To Support Social Participation In Later Lifementioning
confidence: 99%